Comparing the Efficiency of Islamic and Conventional Banks Based on the Evidence from Malaysia - Muhamad Azhari Wahid (Universiti Sains Islam Malaysia, 2024)
This paper examines whether Malaysian Islamic banks are more efficient relative to conventional banks over the period of 2004-2013. Also, the study investigates the determinants of efficiency for Islamic and conventional banks in Malaysia during the period of observation. In doing so, we employed two stages of analysis. First, data envelopment analysis (DEA) method was used to measure technical efficiency (TE) of Islamic and conventional banks. Second, a panel data regression analysis was estimated to examine the determinants of efficiency for both types of banks. Although the non- parametric test indicates that TE of conventional banks was different and higher than Islamic banks, the regression analysis based on size of banks suggests that this is only true for small banks. However, for sample of large banks, the result reveals that Islamic banks were technically more efficient that conventional banks. Further analysis reveals that factors which have negative effect on the efficiency of Islamic and conventional banks in Malaysia were level of capitalization, asset quality, inflation and post-crisis dummy variables. In contrast, factors which have positive effect on the efficiency of both banking systems were GDP, non- interest income and pre- crisis dummy variables. In addition, several other determining factors specific for Malaysian Islamic banks were bank size which has positive effect, and non- interest expenses which has negative effect on bank efficiency. While determining factors specific for Malaysian conventional banks were bank size which have negative effect, and non-interest expenses which has positive effect on bank efficiency.